How is the Sanitary Home Industry Sustainability through the Implementation of Economic Education? - Widya Eka Puspitasari; Sri Umi Mintarti; Lisa Rokhmani (Jurnal Pendidikan Humaniora, 2021)
Abstract: This reasearch seeks to explore the sustainability of Sanitair's business in terms of the economics education of business practitioners. It was conducted by using qualitative approach of phenomenology. The research informants was the owner who run the businesses for more than 20 years. The results showed that business sustanbility developed after implementing economics education in terms of production, distribution activities, and consumption of raw materials, wider range of product sales, also open the new businesses due to the high demand toward the product.Keywords: business Suistanbility, economics Education, business management, business activityAbstrak: Tujuan penelitian adalah menganalisis keberlangsungan usaha Sanitair ditinjau dari penerapan pendidikan ekonomi para pelaku usaha. Penelitian ini menggunakan metode kualitatif jenis fenomenologi. Informan penelitian adalah pelaku usaha sanitair yang memiliki usaha lebih dari 20 tahun. Hasil penelitian menunjukkan keberlangsungan usaha sanitair pelaku usaha dikategorikan baik dan berkembang setelah menerapkan pendidikan ekonomi dalam hal aktivitas produks, distribusi, dan konsumsi bahan baku dibuktikan dengan semakin berkembangnya usaha sanitair, jangkauan penjualan produk lebih luas, serta pelaku usaha dapat membuka usaha baru dikarenakan omzet dari usaha meningkat.Kata kunci: keberlangsungan usaha, pendidikan ekonomi, manajemen bisnis, aktifitas bisnis